KAJIAN PENGEMBANGAN INDUSTRI RUMAH TANGGA KERIPIK DESA WONODADI KULON PACITAN - I Made Kastiawan; Tiurma Wiliana Susanti P; Rini Rahayu Sihmawati (JPM17: Jurnal Pengabdian Masyarakat, 2015)
chips Household Industry in Wonodadi Kulon-Pacitan village has a good prospect, it is because in the area and its surroundings have quite abundant raw materials. Long enough household businesses was developed by a group of villagers, but the development of this business is still very slow, it is possible because the business is run as a sideline. With a variety of approaches and provides an insight into this business opportunity, through IbM program, partners started running this business more seriously, and to make this effort as part of family activities for their livelihood. The group wants to spread to a wider market, then the team IbM provide assistance in terms of business management, financial and marketing. On the other hand, the team IbM provide additional technology is the method of cooking vacuum (vacuum frying). This technology is appropriate given with respect to the amount of fruit that has a fairly expensive price such as mango, pineapple, papaya, durian and bark generated this area. With the harvest is abundant and it price is cheap, then the partner is expected to help farmers to receive the crops which is then processed into fruit chips which have a higher selling price. To support the sales and make consumers more interested, then the appearance of the product to be one of arable IbM team. Therefore, IbM team gave a training to make packaging labels. Similarly, in order to products marketed accountable, trustworthy, and safe for consumption, then the team IbM assisting partners to do an assessment and permits PIRT.Keywords: Chips Industrial, Vacuum Frying Machine, Label Products, PIRTÂ